Comparison of Advanced Modulation Techniques of Free Space Optical Link for Ground-to-Train Communication - Hyder Ali Tajuddin, Intan Najihah; Othman, Maisara; Homam, Mariyam Jamilah; Jamil, Ansar; M. Audah, Lukman Hanif; Abdullah, Mohammad Faiz Liew; Abd Wahab, Mohd Helmy; Mohd Shah, Shaharil; Zainal Abidin, Zuhairiah (International Journal of Integrated Engineering, 2025)
Nowadays, mundane tasks are becoming more 'on-the-go', leading to the increasing popularity of public transport like high-speed trains. Internet access for these trains has increased, requiring the deployment of free space optical (FSO) communications in ground-to-train (G2T) communication. However, there is a lack of research on FSO links for railway communications. Single tracks mathematical models have been applied to address this need. Multiple attenuation intensities were tested for various weather conditions (clear, drizzle, strong rain, rainstorm and light fog), and three modulation techniques which are NRZ, OFDM 4-QAM, and OFDM 4-QPSK at 10 Gbps were implemented to improve link performance. Geometric parameters were optimized, and models were assessed for transmission distance and received optical power. The performance of the modulation techniques has been evaluated at BER of 1x10-9 for NRZ and BER of 2.8x10-3 for OFDM 4-QAM and OFDM 4-QPSK using the Optisystem®. Simulation results show that with a slightly lower BER, in strong rain condition for 4-QPSK have a higher ROP of -2.7 dBm compared to -3.7 dBm for 4-QAM. However, a few improvements can be made in future research, such as using multi transmitter concepts such as Multiple Input Single Output (MISO) to improve G2T-FSO performance and extend transmission distance coverage.